The Legal Concept of Construction Dispute Resolution through Adjudication in Indonesia: A Comparative Study - Ahmad Rizal; Huala Adolf; Djuhaendah Hasan; Ida Nurlinda (International Journal of Supply Chain Management, 2021)
This study aims to analyze (1) the dispute of construction service through adjudication in Malaysia and New South Wales, Australia; and (2) the legal conception of construction dispute through adjudication in Indonesia. The methodology used in this research was the normative legal jurisdiction with the statute, conceptual, comparison, and comparative approach. The results show that (1) the dispute of construction service through adjudication in Malaysia and New South Wales, Australia, is a legal process where the appointed adjudicator is responsible to solve the dispute between the conflicted parties. Furthermore, the adjudication process is carried out by assigning a dispute adjudication board. Since there is no obstruction in the fieldwork when this process is applied, therefore it is considered more effective; and (2) the legal conception of construction dispute through adjudication in Indonesia is preferable to reflect on CIPAA 2012 which is successfully applied in Malaysia.